The Effectiveness of a Holistic Approach in Early Children's Language Development - Permatasari, Tisya; Susijati, Susijati; Andiyanti, Susi Sri (Pusdikra-Publishing.com, 2023)
This study investigates the effectiveness of a holistic approach to early childhood language development through an extensive literature review. The holistic approach integrates cognitive, emotional, social, and physical dimensions to promote comprehensive language growth in young children. Findings suggest that environments providing rich verbal stimulation and active social interaction are pivotal in enhancing children's vocabulary and language comprehension. Frequent, positive interactions with adults and peers significantly support the development of speaking skills and verbal expression. Additionally, family involvement in daily language activities plays a crucial role in optimizing language development outcomes. Despite strong evidence supporting the holistic approach, this study acknowledges the limitation of relying solely on literature reviews and emphasizes the need for further empirical research, including case studies and experimental studies. Such research is necessary to validate the effectiveness of the holistic approach and to explore its practical applications in diverse educational contexts. The research highlights the significant potential of the holistic approach in fostering comprehensive language development and calls for continued investigation to refine and enhance educational practices based on these findings.